2021
DOI: 10.1177/08971900211017857
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Medications Used for Hospitalized Patients With Sleep Disturbances: A Frequency Analysis and Literature Review

Abstract: Purpose: Poor sleep during hospitalization is common and implicated in worse patient outcomes. Despite implementation of non-pharmacologic techniques, medications are still frequently required. The study objective is to assess the frequency of new medications administered for sleep in hospitalized patients and to review literature evaluating these drug therapies in the inpatient setting. Methods: This retrospective study included adult inpatients if they received a new medication for sleep during a 5-day perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Our results regarding sedatives/hypnotic medicines showed that most patients frequently start these medications during hospitalization, which is undesirable, and values reached are higher than the 8% reported by White et al in the USA. 10 In their study, the most commonly prescribed drug was melatonin (70.5%), followed by benzodiazepines (9.6%) and zolpidem (8.4%). 10 Although melatonin is an interesting drug to be used, it is not available in our hospital.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our results regarding sedatives/hypnotic medicines showed that most patients frequently start these medications during hospitalization, which is undesirable, and values reached are higher than the 8% reported by White et al in the USA. 10 In their study, the most commonly prescribed drug was melatonin (70.5%), followed by benzodiazepines (9.6%) and zolpidem (8.4%). 10 Although melatonin is an interesting drug to be used, it is not available in our hospital.…”
Section: Discussionmentioning
confidence: 95%
“…10 In their study, the most commonly prescribed drug was melatonin (70.5%), followed by benzodiazepines (9.6%) and zolpidem (8.4%). 10 Although melatonin is an interesting drug to be used, it is not available in our hospital. 16 A positive point to notice is that hydroxyzine is no longer used prior and during hospitalization in elderly patients, since previous data from our department showed that hydroxyzine was a frequent inappropriately prescribed drug.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…12,14 Despite clinical guidelines recommending nonpharmacologic or less risky pharmacologic alternatives, they are often prescribed on night shifts to efficiently handle agitation, delirium or sleep concerns. [15][16][17][18] Unfortunately, suboptimal prescribing can lead to an increased risk of poor clinical outcomes, such as falls, particularly in older adults. 13,19,20 We believed that some of suboptimal prescribing could be related to how physicians, particularly medical residents, make decisions during times of stress.…”
Section: Introductionmentioning
confidence: 99%
“…System 1 thinking may be particularly problematic for potentially inappropriate medications with well‐known adverse effects, such as anti‐psychotics, benzodiazepines and sedative hypnotics (e.g., zolpidem or eszopiclone), which continue to be widely used despite recommendations from numerous professional societies against their use 12,14 . Despite clinical guidelines recommending nonpharmacologic or less risky pharmacologic alternatives, they are often prescribed on night shifts to efficiently handle agitation, delirium or sleep concerns 15–18 . Unfortunately, suboptimal prescribing can lead to an increased risk of poor clinical outcomes, such as falls, particularly in older adults 13,19,20 .…”
Section: Introductionmentioning
confidence: 99%